Case Report: Novel CNGA3 compound heterozygous variants cause achromatopsia in three patients from a family - Zhou, Xiaoqiang; Zhou, Yasi; Wu, Shuijuan; Guo, Xiaoling; Yao, Liangfeng; Yang, Xingkun (Frontiers in Genetics, 2024)
This study report a novel missense variant in the cyclic nucleotide-gated channel 3 (CNGA3) gene identified by targeted gene panel sequencing approach in a Chinese family with achromatopsia. The proband, a 24-year-old female, with normal intelligence, motor development and speech abilities exhibited nystagmus, amblyopia, photophobia, and indistinguishable colors. In addition, the two sisters of the proband had the same clinical symptoms, which means that three patients from a family with a monochromasia clinical diagnosis. Based on the family situation, the proband came to our hospital for facilitate genetic counseling. Genetic analysis using targeted gene panel sequencing was conducted to confirm causative variants. Compound heterozygous variants, including the novel missense c.524T>A (p.Ile175Asn) and the know missense variant c.829C>T (p.Arg277Cys), were identified in CNGA3. These variants represent the genetic defects associated with achromatopsia in this family.